Mycotoxins in broiler production - Oliveira, Helder Freitas de; Souto, Cristielle Nunes; Martins, Poliana Carneiro; Di Castro, Izabela Cruvinel; Mascarenhas, Alessandra Gimenez (Revista de Ciências Agroveterinárias, 2018)
The occurrence of mycotoxins has become a problem to be discussed, due to its harmfulness to humans and animal’s health, and may be an obstacle to the poultry economy. Mycotoxins are toxic metabolites produced by certain species of fungi and may contaminate food. Aflatoxins are mainly produced by Aspergillus flavus and Aspergillus parasiticus, and B1, B2, G1 and G2 are its best known types. Fumonisin, with its B1, B2 or B3 types, are produced by Fusarium, while ochratoxin A is produced by Penicillium and Aspergillus. The main trichothecenes mycotoxins are T-2 toxin, deoxynivalenol and diacetoxyscirpenol. Zearalenone, produced by different species of Fusarium fungi affects chickens only when they are exposed to extremely high levels of contamination. Generally, immunosuppression, hepatotoxicity and nephrotoxicity as a decrease in performance and production gains are the most observed effects. There are several laboratory methods that can be used for the determination of mycotoxins. In order to control the contamination, it is necessary to adopt proper farming practices which prevent fungi growth. Once grains and feed are contaminated, biological, physical and/or chemical decontamination methods may be employed, although the physical process with adsorbents mixed to the feed is more widely used. Due to the importance of mycotoxins to poultry production, it is necessary to adopt measures to prevent contamination, and also develop a control and an anti-fungal growth and toxin production program by reviewing the critical points favorable to the emergence of toxin-producing fungi.